Fostering Social Awareness and Responsibility Through Educational Entrepreneurship - Fitria, Adilah Wina; Wahira, Wahira (Ridwan Institute, 2024)
Social entrepreneurship has emerged as a strategic approach in education to address various social issues while fostering social awareness and responsibility among students. This study aims to analyze the role of social entrepreneurship in education as an effective learning tool to cultivate pro-social attitudes through a comprehensive theoretical approach. Drawing on Social Learning Theory and Experiential Learning, this paper examines how the integration of social entrepreneurship into educational curricula can develop critical awareness of social issues and encourage responsible actions among learners (Bandura, 1977; Kolb, 1984). The findings indicate that the implementation of social entrepreneurship in education not only equips students with entrepreneurial skills but also reinforces ethical values and social responsibility, contributing to character development in the younger generation. This is supported by literature showing increased social awareness and altruistic behavior resulting from participation in social entrepreneurship projects (Hockerts, 2018; Tracey & Phillips, 2007). Therefore, integrating social entrepreneurship into education holds significant potential to not only produce successful entrepreneurs but also leaders committed to creating positive social impact. This study recommends the development of a more holistic and collaborative curriculum to ensure that social entrepreneurship becomes an integral part of higher education.